2001
DOI: 10.1097/00002030-200107270-00004
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein and transporter MRP1 reduce HIV protease inhibitor uptake in CD4 cells: potential for accelerated viral drug resistance?

Abstract: The overexpression of multidrug transporters significantly reduces the accumulation of protease inhibitors at this major site of virus replication, which, potentially, could accelerate the acquisition of viral resistance. Targeted inhibition of P-gp may represent an important strategy by which this problem can be overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 26 publications
4
104
1
Order By: Relevance
“…Saquinavir, nelfinavir, and ritonavir all showed significant nonspecific binding, which was corrected for throughout this study to provide true kinetic parameters. Nelfinavir has previously been shown to exhibit a higher degree of intracellular accumulation compared with other PIs (Jones et al, 2001;Khoo et al, 2002). Significantly higher metabolic rates (corresponding to lower K m values) were observed when the kinetics of saquinavir, nelfinavir, and ritonavir in rat liver microsomes were compared with suspended rat hepatocytes, ranging from 6-fold lower for ritonavir and saquinavir to 30-fold lower for nelfinavir.…”
Section: Hepatocellular Uptake and Drug Metabolic Clearancementioning
confidence: 96%
See 1 more Smart Citation
“…Saquinavir, nelfinavir, and ritonavir all showed significant nonspecific binding, which was corrected for throughout this study to provide true kinetic parameters. Nelfinavir has previously been shown to exhibit a higher degree of intracellular accumulation compared with other PIs (Jones et al, 2001;Khoo et al, 2002). Significantly higher metabolic rates (corresponding to lower K m values) were observed when the kinetics of saquinavir, nelfinavir, and ritonavir in rat liver microsomes were compared with suspended rat hepatocytes, ranging from 6-fold lower for ritonavir and saquinavir to 30-fold lower for nelfinavir.…”
Section: Hepatocellular Uptake and Drug Metabolic Clearancementioning
confidence: 96%
“…In vivo, hepatocytes express both efflux and uptake transporters, and it is important to consider that the apparent uptake rate may be affected by efflux rate, especially because PIs are well documented to be substrates for efflux transporters (Srinivas et al, 1998). An increase in uptake rate in cell lines expressing both P-gp and uptake transporters has been observed using P-gp inhibitors (Jones et al, 2001;Su et al, 2004). In freshly isolated rat hepatocytes, expression of efflux transporters may be significantly lower than in vivo due to downregulation and internalization of the apical membrane, and although P-gp has been detected on the hepatocyte apical membrane after isolation using immunohistochemical techniques, it is at a lower abundance than in vivo (Bow et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Because the equilibrium between extra-and intracellular concentrations is often regulated by efflux proteins, changes in efflux protein activity may alter the sensitivity of the cells to these compounds like it has been demonstrated for saquinavir, ritonavir, and lopinavir (12,18,19). Decreased intra-cellular availability of the drug in response to upregulation of efflux transporters will therefore shift IC 50 values for antiproliferative effects towards higher (extracellular) concentrations and thus protect the cells.…”
Section: Growth Inhibition Assaysmentioning
confidence: 99%
“…Due to the short half-lives of the PI's in rodents, 33) if auto-inhibition was not present and if steady-state concentrations had been reached prior to day 7, we would have expected plasma levels to remain more or less constant. 33) Recent studies found that P-gp inhibition could possibly have a superior influence over CYP3A4 modification in altering pharmacokinetics. 34) Over time, an equilibrium is reached and an increase in levels are observed.…”
Section: Discussionmentioning
confidence: 99%